Possible actions of methionine on embryonic development and postnatal phenotype of calves produced after embryo transfer - Masroor Sagheer; Quinn A. Hoorn; Oscar A. Ojeda-Rojas; Jeremy Block; Abigail J. Sproull; Daniella Heredia; Camila J. Cuellar; Tatiane S. Maia; McKenzie LJ. Haimon; Mariângela Bueno Cordeiro Maldonado; João H. Bittar; Angela M. Gonella-Diaza; et al. (Theriogenology, 2026)

Potential Prevalence of Front-of-Package Labels on Packaged Foods in a Supermarket Chain in the Northeast United States Under Two Proposed Labeling Systems - Joshua Petimar; C. Ross Hatton; Yutong Zhang; Alyssa J. Moran; Anna H. Grummon; Lauren P. Cleveland; Jason P. Block; Aviva A. Musicus (Journal of the Academy of Nutrition and Dietetics, 2026)

Quinol C-methyltransferases from extant species of early cyanobacterial lineages shed light on the emergence of plastoquinone in oxygenic phototrophs - Gabriella Dickinson; Lauren R. Stutts; Scott Latimer; Nathan Smith; Zhaniya Batyrshina; Monika Kula-Maximenko; Ireneusz Ślesak; Anna K. Block; Mark A. Wilson; Gilles J. Basset (Photosynthesis Research, 2025)

A quasi-differential measurement of neutron scattering from tantalum between 0.65 MeV and 20 MeV - Gregory J. Siemers; Yaron Danon; Sukhjinder Singh; Katelyn C. Keparutis; Peter J. Brain; Benjamin H. Wang; Adam M. Daskalakis; Devin P. Barry; Michael J. Rapp; Robert C. Block (Annals of Nuclear Energy, 2025)

Deep diving behaviour in oceanic manta rays and its potential function - Calvin S. Beale; Ferawati Runtuboy; Abraham B. Sianipar; Angela J. E. Beer; Kadarusman; Mark V. Erdmann; Edy Setyawan; Lydia Green; Clinton A. J. Duffy; Samantha Andrzejaczek; Barbara A. Block; Kerstin Forsberg; et al. (Frontiers in Marine Science, 2025)
Deep dives are performed by a range of marine megafauna, yet their function remains poorly understood. Proposed functions include foraging, predator avoidance, and navigation, but limited fine-scale data have hindered rigorous testing of these hypotheses. Here, depth time-series data from eight recovered and 16 non-recovered satellite tags deployed on oceanic manta rays ( Mobula birostris ) in Indonesia, Peru, and New Zealand were examined to characterise extreme dives and identify their potential function. From a total of 46,945 dives, 79 extreme dives (>500 m) were recorded, 11 of which were documented from recovered tags and associated high sampling frequency. Extreme dives were distinguished by rapid descents (up to 2.9 m s⁻¹), brief horizontal “steps” at depth, gradually slowing ascents, and extended periods spent near the surface both before and after diving. Unlike typical foraging dives, no substantial bottom phase was observed, and vertical oscillations—expected if feeding at depth—were absent. Extreme dives also occurred more frequently with increasing distance from the continental shelf edge as well as preceding periods of high 72h distance travelled, indicating they may inform subsequent movements. We propose that extreme dives enable oceanic manta rays to survey the properties of the water column, likely gathering environmental cues—such as temperature, dissolved oxygen, or geomagnetic gradients—to guide navigation and/or the decision to leave or remain in a general area. In open-ocean environments where external reference points are absent, such costly but infrequent dives may provide critical information for long-distance movements. Our results offer new insights into the role of extreme diving behaviour in oceanic manta rays and highlight the importance of fine-scale data for understanding deep-diving behaviours in marine megafauna.

Functional assessments of short-term spatial memory in the Dog Aging Project identify strong associations with age that are not moderated by body mass - Stephanie H. Hargrave; Amber J. Keyser; Emma Kristal; Gene E. Alexander; Theadora A. Block; Emily E. Bray; Laura E. L. C. Douglas; Brenda S. Kennedy; Daniel E. L. Promislow; David A. Raichlen; Dog Aging Project Consortium; Evan L. MacLean (GeroScience, 2025)

A classification system for wounds and scars observed on white sharks (Carcharodon carcharias) - Scot D. Anderson; Paul E. Kanive; Taylor K. Chapple; Samantha Andrzejaczek; Barbara A. Block; Salvador J. Jorgensen (Frontiers in Marine Science, 2025)

The herbivore-inducible coumarate-CoA ligase 5 (Zm4CL5) in maize contributes to the production of non-lignin phenylpropanoids - Hui Liu; Zachary Gorman; Ariel Sorg; Hailey Maurer; Sanket Shinde; Esha Kaler; Gilles J. Basset; Joe Louis; Anna K. Block (Planta, 2025)

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

First satellite track of a juvenile shortfin mako shark (Isurus oxyrinchus) in the Mediterranean Sea - Brendan D. Shea; Taylor K. Chapple; Khaled Echwikhi; Chiara Gambardella; Jeremy F. Jenrette; Stefano Moro; Robert J. Schallert; Barbara A. Block; Francesco Ferretti (Frontiers in Marine Science, 2024)

The origin and metabolic fate of 4-hydroxybenzoate in Arabidopsis - Zhaniya Batyrshina; Anna K. Block; Gilles J. Basset (Planta, 2024)

Developing a range-wide sampling framework for endangered species: a case study with light-footed Ridgway’s rail - Bryan S. Stevens; Courtney J. Conway; Kimberly A. Sawyer; Lauren Kershek; Giselle Block; Sandra Hamilton; Rebecca Kolstrom (Biodiversity and Conservation, 2024)
Monitoring provides the foundation for evaluating recovery of endangered species, yet many species lack monitoring programs designed to integrate a species’ unique attributes, specific monitoring objectives, and principles of statistical sampling theory. We developed a framework for monitoring and assessment of endangered light-footed Ridgway’s rails ( Rallus obsoletus levipes ) across their U.S. range, relative to multi-scale recovery goals. We created spatially explicit sample units and a sampling frame covering all potential habitat to facilitate range-wide probability sampling, and also built a model of the call-broadcast process commonly used to survey marsh birds that included heterogeneity in availability for detection and conditional detectability for each bird during each survey. We used the model to simulate 96 sampling strategies that included different levels of replication, multiple approaches for sample allocation amongst strata, and both simple random and weighted probability sampling (i.e., weights proportional to local rail abundance) of sample units within strata. Effective monitoring surveyed ≥ 20–30% of the sampling frame on ≥ 3 occasions, with weighted sample selection and more targeted sampling (50% of units) for strata that are key to species recovery. We also tested Bayesian N-mixture models for estimating abundance and show that multiple models provide reasonable estimates. This work lays the foundation for statistical sampling and multi-scale population estimation for an endangered bird, and for refinement of abundance estimation models. Moreover, this work provides a replicable process for building customized and statistically defensible sampling frameworks to assess recovery of endangered species that can be used for other sensitive species.

On the tracks of white sharks in the Mediterranean Sea - Francesco Ferretti; Brendan D. Shea; Chiara Gambardella; Jeremy F. Jenrette; Stefano Moro; Khaled Echwikhi; Robert J. Schallert; Austin J. Gallagher; Barbara A. Block; Taylor K. Chapple (Frontiers in Marine Science, 2024)
White sharks ( Carcharodon carcharias ) are among the most widespread, charismatic, and studied predators in the ocean. However, their conservation status is concerning in many ocean sectors, most notably the Mediterranean Sea, which hosts one of the least known and most endangered populations globally. Though they were historically abundant and widely distributed in the region, Mediterranean white sharks have declined to dangerously low abundance levels, impacted by centuries of coastal and, more recently, industrial fishing. The IUCN lists this species as Critically Endangered in the region, but information about its current abundance and ecology is scarce, hindering effective management and conservation. Here, we describe our initial effort to find and track the remaining Mediterranean white sharks and report what we have learned from these activities. In 2021-2023, we conducted three pilot expeditions in the Sicilian Channel, covering four major sites, collecting 159 eDNA samples, and carrying out 359 hrs of pelagic mid-water baited video surveys, 43 hours of deep-water benthic baited video surveys, and 111 hrs of fishing. Baited video surveys detected 42 species of bony fishes, elasmobranchs, marine mammals, and turtles. We detected white sharks at four sites from eDNA samples. Though we did not observe white sharks directly, these activities supported the identification of one of the last strongholds of this population in the region and started a multi-institutional white shark conservation program in the Mediterranean Sea, aiming to track the last white sharks in the region, estimate their abundance and extinction risk, characterize the species’ ecology and inform management and conservation.

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

The role of explicit knowledge in compensating for a visuo-proprioceptive cue conflict - Anna Hsiao; Hannah J. Block (Experimental Brain Research, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Satellite tagging insights into the seasonal movements and behavior of Mediterranean spearfish (Tetrapturus belone, Istiophoridae) - Danilo Malara; Pietro Battaglia; Martin C. Arostegui; Jonathan J. Dale; Barbara A. Block; Camrin D. Braun; Massimo Brogna; Silvestro Greco; Teresa Romeo (Frontiers in Marine Science, 2024)
The Mediterranean spearfish ( Tetrapturus belone ) is a highly migratory predator, also exploited by commercial and recreational fisheries although its catches are poorly reported. The fishing pressure on this species is currently unknown because catch and landing data are fragmentary. Furthermore, more ecological information (e.g. migratory movements) is needed to establish eventual management measures, and ICCAT has not examined the population status yet. Understanding species migratory movements is crucial for addressing conservation challenges and supporting management decisions. In this study we investigated the migratory movements, seasonal patterns, vertical behavior, and thermal preference of T. belone , with the aim to improve information on its ecology and behavior. Overall, six individuals were tagged in the Strait of Messina and Tyrrhenian Sea with pop-up satellite tags and their movements were mainly restricted to the central Mediterranean. Utilization distributions derived from geolocation revealed an overall and seasonal importance of the Tyrrhenian Sea and Strait of Sicily, as well as variability in winter habitat use. While the fish exhibited similar depth preference, spending the majority of time at depths ≤ 10 m, we observed that the Mediterranean spearfish is also able to perform sporadic deep dives below 200 m. Vertical movement showed a bimodal pattern common in other billfish species, characterized by occupation of shallower, warmer waters during the night and deeper, cooler waters during the day. This research increases knowledge on the migration ecology and habitat preference of T. belone which is important for management of this understudied species.

Effects of mycobacterium cell wall fraction on embryo development following in vitro embryo production and pregnancy rates following embryo transfer in virgin dairy heifers - W. Brown; M. Oliveira; R. Reis Silva; K. Woodruff; B. Bisha; D. Demetrio; J. Block (Theriogenology, 2024)

Maize terpene synthase 1 impacts insect behavior via the production of monoterpene volatiles β-myrcene and linalool - Jessica P. Yactayo-Chang; Geoffrey T. Broadhead; Robert J. Housler; Marcio F.R. Resende; Kashish Verma; Joe Louis; Gilles J. Basset; John J. Beck; Anna K. Block (Phytochemistry, 2024)

Tagging of Atlantic bluefin tuna off Ireland reveals use of distinct oceanographic hotspots - Camille M.L.S. Pagniello; Niall Ó Maoiléidigh; Hugo Maxwell; Michael R. Castleton; Emilius A. Aalto; Jonathan J. Dale; Robert J. Schallert; Michael J.W. Stokesbury; Ronán Cosgrove; Simon Dedman; Alan Drumm; Ross O'Neill; et al. (Progress in Oceanography, 2023)

Effect of visuo-proprioceptive mismatch rate on recalibration in hand perception - Reshma Babu; Trevor Lee-Miller; Manasi Wali; Hannah J. Block (Experimental Brain Research, 2023)

Connectivity between white shark populations off Central California, USA and Guadalupe Island, Mexico - Paul E. Kanive; Jay J. Rotella; Taylor K. Chapple; Scot D. Anderson; Mauricio Hoyos-Padilla; Abbott Peter Klimley; Felipe Galván-Magaña; Samantha Andrzejaczek; Barbara A. Block; Salvador J. Jorgensen (Frontiers in Marine Science, 2023)
Marine animals often move beyond national borders and exclusive economic zones resulting in a need for trans-boundary management spanning multiple national jurisdictions. Highly migratory fish vulnerable to over-exploitation require protections at international level, as exploitation practices can be disparate between adjacent countries and marine jurisdictions. In this study we collaboratively conducted an analysis of white shark connectivity between two main aggregation regions with independent population assessment and legal protection programs; one off central California, USA and one off Guadalupe Island, Mexico. We acoustically tagged 326 sub-adult and adult white sharks in central California (n=210) and in Guadalupe Island (n=116) with acoustic transmitters between 2008-2019. Of the 326 tagged white sharks, 30 (9.20%) individuals were detected at both regions during the study period. We used a Bayesian implementation of logistic regression with a binomial distribution to estimate the effect of sex, maturity, and tag location to the response variable of probability of moving from one region to the other. While nearly one in ten individuals in our sample were detected in both regions over the study period, the annual rate of trans-regional movement was low (probability of movement = 0.015 yr -1 , 95% credible interval = 0.002, 0.061). Sub-adults were more likely than adults to move between regions and sharks were more likely to move from Guadalupe Island to central California, however, sex, and year were not important factors influencing movement. This first estimation of demographic-specific trans-regional movement connecting US and Mexico aggregations with high seasonal site fidelity represents an important step to future international management and assessment of the northeastern Pacific white shark population as a whole.

Assignment of tracks from tagged Atlantic bluefin tuna Thunnus thynnus to potential stocks using behavioural differences and habitat partitioning - Simon Dedman; Emilius A. Aalto; Michael J. W. Stokesbury; Robert J. Schallert; Michael R. Castleton; Barbara A. Block (Frontiers in Marine Science, 2023)
Introduction Atlantic bluefin tuna (ABT) are large, migratory pelagic predators of high economic importance. ABT are currently managed as two independent stocks assigned to discrete spawning areas (Gulf of Mexico, and Mediterranean); however, stock overlap outside spawning areas makes accurate assignment of catch to stock-of-origin difficult. Methods Within this two-stock paradigm, we characterised stock-specific spatial distributions and behaviours by comparing habitat usage and vertical movement behaviours of 118 electronically tagged adult ABT spatially assigned to the GOM and Med spawning grounds. These spatial and behavioural differences were used in tests to probabilistically assign unknown individuals (which did not visit the GOM/Med spawning areas) to a stock. Results This new methodological approach using existing tag data, enables increased assignment of a track to a potential stock, to be achieved before genetic assignments. We identified certain markedly different movement patterns, range extents, depth use preferences (and associated area usage), migration directness and speeds, corresponding distance from shore, and mesopelagic-layer visitation. The probabilistic assignment approach had 97% in-bag testing accuracy, then assigned 190 individuals to a stock, doubling the number of assigned stock-of-origin tracks in our dataset, and potentially revealing novel movement and behaviour patterns among pre-spawning-age ABT. Discussion This approach can be easily adapted to other study species, more stocks, and different testing variables, hopefully serving as a useful addition to the fisheries management toolkit.

Prion strains: shining new light on old concepts - Alyssa J. Block; Jason C. Bartz (Cell and Tissue Research, 2023)

Large scale seasonal forecasting of peak season algae metrics in the Midwest and Northeast U.S. - Maxwell R.W. Beal; Grace M. Wilkinson; Paul J. Block (Water Research, 2023)

Rainy season precipitation forecasts in coastal Peru from the North American Multi‐Model Ensemble - Stephen J. Vavrus; Fuyao Wang; Paul Block (International Journal of Climatology, 2022)
We assessed operational forecasts of rainy season (January–March [JFM]) precipitation over coastal Peru from seven global climate models (GCMs) in the North American Multi‐Model Ensemble (NMME) from 1982 to 2020. Similar to previous representations by GCMs, regional climate models, and atmospheric reanalyses, the NMME models produce excessive precipitation (more than twice the observed values) over all of coastal Peru. Based on a set of commonly used metrics (correlation, mean error, RMSE, and Heidke skill score), there is a wide range in accuracy among the NMME models. As expected, forecast accuracy degrades with increasing lead time from December to July, but the rate of decline varies greatly by region and among models. The cause(s) of differences in model performance remains unclear, but resolution does not appear to be a significant factor. Highest forecast skill is found for southwestern Peru (correlations with observations are significant at all lead times), probably because of its stronger relationship between rainfall and El Niño–Southern Oscillation (ENSO), and lowest skill occurs for west‐central Peru (insignificant correlations at all lead times). The distribution of interannual rainy season precipitation in northwestern Peru is extremely positively skewed (skewness >2), making evaluation of forecasts difficult from only a few years that deviate strongly from the mean. Improved correlations with observations across regions are generally found by subsetting multi‐model mean forecasts using the better‐performing models. Over northwest Peru at short lead times, NMME rainy season precipitation forecasts outperform a simple statistical correlation between JFM rainfall and ENSO, but not at longer leads, while NMME's forecasts for west‐central Peru underperform statistical correlations at all lead times. Over southwest Peru, the NMME models are consistently more skilful than a statistical correlation, and these differences become larger with increasing lead time.

Informing Management of Atlantic Bluefin Tuna Using Telemetry Data - Rebecca Whitlock; Robert J. Schallert; Michael J. W. Stokesbury; Michael Castleton; Barbara A. Block (Frontiers in Marine Science, 2022)
Sustainable management of exploited marine fish and wildlife populations requires knowledge about their productivity. Survival from natural causes of mortality is a key component of population productivity, but is notoriously difficult to estimate. We evaluate the potential for acoustic telemetry as a long-term monitoring tool to estimate rates of natural mortality. We present a Bayesian multistate mark-recapture model for telemetry data collected over a decade from 188 Atlantic bluefin tuna ( Thunnus thynnus) and apply it to estimate the rate of natural mortality using only acoustic tag detections for all animals, or using acoustic tag detections for 96 single-tagged tuna plus acoustic tag detections combined with estimated positions from pop-up satellite archival tags for 92 double-tagged animals. We support the model for bluefin tuna with a simulation study to quantify bias in estimates of population dynamics parameters and investigate the effect of auxiliary information from satellite tagging on mortality rate estimates for different acoustic tag detection probability scenarios. We obtained posterior estimates of the instantaneous annual natural mortality (survival) rate across a decade of tagging for Atlantic bluefin tuna of 0.17 yr -1 (0.84 yr -1 ) both using only acoustic tagging data, and using a combination of acoustic and satellite tagging data. Use of a prior implying a higher rate of fishing mortality yielded an instantaneous annual natural mortality (survival) estimate of 0.10 yr -1 (0.90 yr -1 ), with combined acoustic and satellite tag data. Results from the simulation study indicate that the use of satellite tags can improve the precision and accuracy of estimates of detection probabilities, area-specific movement probabilities and mortality rates, where the extent of the improvement depends on true underlying acoustic tag detection probabilities. Our work demonstrates that long-term acoustic tagging data sets have strong potential for monitoring of highly migratory marine fish and wildlife populations, providing information on a number of key parameters, including survival and movement rates. However, improved information on tag reporting rates or fishing mortality is needed to better separate natural and fisheries mortality for Atlantic bluefin tuna.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Multi-Decadal High-Resolution Data Reveal the Cryptic Vertical Movement Patterns of a Large Marine Predator Along the Californian Coast - Samantha Andrzejaczek; Taylor K. Chapple; Salvador J. Jorgensen; Scot D. Anderson; Michael Castleton; Paul E. Kanive; Timothy D. White; Barbara A. Block (Frontiers in Marine Science, 2022)
Over the last two decades, satellite tagging of adult and sub-adult white sharks Carcharodon carcharias off the west coast of North America has revealed a predictable onshore-offshore migratory cycle. Our current understanding of the vertical movements exhibited by white sharks while in their coastal foraging phase in the California Current, however, remains limited. Here, we used recovered datasets from 31 archival satellite tags to quantify vertical habitat use. Tags were deployed on individuals between 2000 and 2018 and recorded depth and temperature data at continuous 1–120 s intervals before being recovered up to a year after deployments. Four satellite-tagged individuals were concurrently tagged with acoustic tags, providing precise location data when detected by acoustic receivers that allowed us to explore how reported vertical habitat use varied spatially. While in the coastal shelf waters, white sharks moved at a mean depth ± SD of 14.3 ± 4.0 m and occupied significantly deeper depths during the day than the night. High individual, temporal and spatial variation was evident in vertical movements, while consistent diel and lunar effects emphasized the importance of light-level driving vertical behavior around hunting sites. The vertical movement behaviors reported here provide knowledge of how white sharks may directly and indirectly interact with their mammalian prey in a dynamic three-dimensional system during their capital foraging phase. Temporal patterns in vertical behavior, for instance, indicated that surface waters during early morning hours are the riskiest place for prey. Combining these novel findings with higher-resolution biologging techniques in future studies will allow us to further contextualize fine-scale vertical movement behaviors of white sharks and examine the specific foraging events that could not yet be isolated in the tagging data.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

A maize leucine-rich repeat receptor-like protein kinase mediates responses to fungal attack - Anna K. Block; Hoang V. Tang; Dorothea Hopkins; Jorrel Mendoza; Ryan K. Solemslie; Lindsey J. du Toit; Shawn A. Christensen (Planta, 2021)

Zea mays Volatiles that Influence Oviposition and Feeding Behaviors of Spodoptera frugiperda - Jessica P. Yactayo-Chang; Jorrel Mendoza; Steven D. Willms; Caitlin C. Rering; John J. Beck; Anna K. Block (Journal of Chemical Ecology, 2021)

Ancillary data from animal-borne cameras as an ecological survey tool for marine communities - T. K. Chapple; D. Tickler; R. C. Roche; D. T. I. Bayley; A. C. Gleiss; P. E. Kanive; O. J. D. Jewell; S. J. Jorgensen; R. Schallert; A. B. Carlisle; J. Sannassy Pilly; S. Andrzejaczek; et al. (Marine Biology, 2021)
Underwater visual surveys represent an essential component of coastal marine research and play a crucial role in supporting the management of marine systems. However, logistical and financial considerations can limit the availability of survey data in some systems. While biologging camera tag devices are being attached to an increasing diversity of marine animals to collect behavioral information about the focal species, the ancillary imagery collected can also be used in analytical techniques developed for diver-based surveys. We illustrate this approach by extracting ancillary data from shark-borne camera tag deployments focused on the behavior of a White shark ( Carcharodon carcharias) off Gansbaai, South Africa, and a Grey Reef shark ( Carcharhinus amblyrhynchos) within the Chagos Archipelago. Within the giant kelp forest environment of Gansbaai we could determine the spatial density of kelp thali and underlying substrate composition. Within the coral reef environment, the animal-borne video allowed us to determine the approximate percent and type of benthic cover, as well as growth form and genus of corals down to the upper mesophotic zone. We also enumerated fish species-level abundance over reef flat and wall environments. We used established dive-survey methods to analyze video data and found the results to be broadly comparable in the two systems studied. Our work illustrates the broad applicability of ancillary animal-borne video data, which is analogous in type and quality to diver-based video data, for analysis in established marine community survey frameworks. As camera tags and associated biologging technologies continue to develop and are adapted to new environments, utilising these data could have wide-ranging applications and could maximise the overall cost–benefit ratio within biologging deployments.

Yellowfin Tuna Behavioural Ecology and Catchability in the South Atlantic: The Right Place at the Right Time (and Depth) - Serena R. Wright; David Righton; Joachim Naulaerts; Robert J. Schallert; Chris A. Griffiths; Taylor Chapple; Daniel Madigan; Vladimir Laptikhovsky; Victoria Bendall; Rhys Hobbs; Doug Beare; Elizabeth Clingham; et al. (Frontiers in Marine Science, 2021)
The yellowfin tuna ( Thunnus albacares: YFT) is a widely distributed, migratory species that supports valuable commercial fisheries. Landings of YFT are seasonally and spatially variable, reflecting changes in their availability and accessibility to different fleets and metiers which, in turn, has implications for sustainable management. Understanding the dynamics of YFT behaviour and how it is affected by biological and ecological factors is therefore of consequence to fisheries management design. Archival and pop-up satellite tags (PSAT) were used in the South Atlantic Ocean around St Helena between 2015 and 2020 to collect information on the movements, foraging and locomotory behaviour of YFT. The study aimed to (1) identify vertical behaviour of YFT within St Helena’s EEZ; (2) assess the timing and depth of potential feeding events and (3) to use the information to inform on the catchability of YFT to the local pole and line fishing fleet. Results indicate that the YFT daytime behaviour shifted between shallow with high incidence of fast starts in surface waters in summer months (December to April), to deep with high incidence of strikes at depth in colder months (May to November). Catchability of YFT was significantly reduced between May and November as YFT spent more time at depths below 100 m during the day, which coincides with a reduction in the quantity of YFT caught by the inshore fleet.

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

Correction to: Genes associated with survival of female bovine blastocysts produced in vivo - A. M. Zolini; J. Block; M. B. Rabaglino; G. Rincon; M. Hoelker; J. J. Bromfield; D. Salilew-Wondim; P. J. Hansen (Cell and Tissue Research, 2020)

Genes associated with survival of female bovine blastocysts produced in vivo - A. M. Zolini; J. Block; M. B. Rabaglino; G. Rincon; M. Hoelker; J. J. Bromfield; D. Salilew-Wondim; P. J. Hansen (Cell and Tissue Research, 2020)

Tracking the response of industrial fishing fleets to large marine protected areas in the Pacific Ocean - Timothy D. White; Tiffany Ong; Francesco Ferretti; Barbara A. Block; Douglas J. McCauley; Fiorenza Micheli; Giulio A. De Leo (Conservation Biology, 2020)
Large marine protected areas (MPAs) of unprecedented size have recently been established across the global oceans, yet their ability to meet conservation objectives is debated. Key areas of debate include uncertainty over nations’ abilities to enforce fishing bans across vast, remote regions and the intensity of human impacts before and after MPA implementation. We used a recently developed vessel tracking data set (produced using Automatic Identification System detections) to quantify the response of industrial fishing fleets to 5 of the largest MPAs established in the Pacific Ocean since 2013. After their implementation, all 5 MPAs successfully kept industrial fishing effort exceptionally low. Detected fishing effort was already low in 4 of the 5 large MPAs prior to MPA implementation, particularly relative to nearby regions that did not receive formal protection. Our results suggest that these large MPAs may present major conservation opportunities in relatively intact ecosystems with low immediate impact to industrial fisheries, but the large MPAs we considered often did not significantly reduce fishing effort because baseline fishing was typically low. It is yet to be determined how large MPAs may shape global ocean conservation in the future if the footprint of human influence continues to expand. Continued improvement in understanding of how large MPAs interact with industrial fisheries is a crucial step toward defining their role in global ocean management.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Contributions of winter foraging to the annual growth of thermally dissimilar fish species - Benjamin D. Block; Jason D. Stockwell; J. Ellen Marsden (Hydrobiologia, 2020)

Uptake and effects of orally ingested polystyrene microplastic particles in vitro and in vivo - Valerie Stock; Linda Böhmert; Elisa Lisicki; Rafael Block; Julia Cara-Carmona; Laura Kim Pack; Regina Selb; Dajana Lichtenstein; Linn Voss; Colin J. Henderson; Elke Zabinsky; Holger Sieg; et al. (Archives of Toxicology, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Estimating Space Use of Mobile Fishes in a Large Marine Protected Area With Methodological Considerations in Acoustic Array Design - Aaron B. Carlisle; David Tickler; Jonathan J. Dale; Francesco Ferretti; David J. Curnick; Taylor K. Chapple; Robert J. Schallert; Michael Castleton; Barbara A. Block (Frontiers in Marine Science, 2019)

Assessment of an anti-scale low-frequency electromagnetic field device on drinking water biofilms - F. Gosselin; L. Mathieu; J.-C. Block; C. Carteret; H. Muhr; F. P. A. Jorand (Biofouling, 2018)

Do elevated blood levels of omega-3 fatty acids modify effects of particulate air pollutants on fibrinogen? - Daniel Croft; Robert Block; Scott J. Cameron; Kristin Evans; Charles J. Lowenstein; Frederick Ling; Wojciech Zareba; Philip K. Hopke; Mark J. Utell; Sally W. Thurston; Kelly Thevenet-Morrison; David Q. Rich (Air Quality, Atmosphere & Health, 2018)

Fungal and herbivore elicitation of the novel maize sesquiterpenoid, zealexin A4, is attenuated by elevated CO2 - Shawn A. Christensen; Alisa Huffaker; James Sims; Charles T. Hunter; Anna Block; Martha M. Vaughan; Denis Willett; Maritza Romero; J. Erik Mylroie; W. Paul Williams; Eric A. Schmelz (Planta, 2018)

False Ring Formation in Bald Cypress (Taxodium distichum) - Carolyn A. Copenheaver; Jonathan D. Matiuk; Lindsey J. Nolan; Morgan E. Franke; Pamela R. Block; Warren P. Reed; Kathryn R. Kidd; Ghalia Martini (Wetlands, 2017)

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

A novel application of multi‐event modeling to estimate class segregation in a highly migratory oceanic vertebrate - T. K. Chapple; T. Chambert; P. E. Kanive; S. J. Jorgensen; J. J. Rotella; S. D. Anderson; A. B. Carlisle; B. A. Block (Ecology, 2016)
Spatial segregation of animals by class (i.e., maturity or sex) within a population due to differential rates of temporary emigration ( TE ) from study sites can be an important life history feature to consider in population assessment and management. However, such rates are poorly known; new quantitative approaches to address these knowledge gaps are needed. We present a novel application of multi‐event models that takes advantage of two sources of detections to differentiate temporary emigration from apparent absence to quantify class segregation within a study population of double‐marked (photo‐identified and tagged with coded acoustic transmitters) white sharks ( Carcharodon carcharias ) in central California. We use this model to test if sex‐specific patterns in TE result in disparate apparent capture probabilities ( p o ) between male and female white sharks, which can affect the observed sex ratio. The best‐supported model showed a contrasting pattern of Pr( TE ) from coastal aggregation sites between sexes (for males Pr[ TE ] = 0.015 [95% CI = 0.00, 0.31] and Pr[ TE ]= 0.57 [0.40, 0.72] for females), but not maturity classes. Additionally, by accounting for Pr( TE ) and imperfect detection, we were able to estimate class‐specific values of true capture probability ( p * ) for tagged and untagged sharks. The best‐supported model identified differences between maturity classes but no difference between sexes or tagging impacts (tagged mature sharks p * = 0.55 (0.46–0.63) and sub‐adult sharks p * = 0.36 (0.25, 0.50); and untagged mature sharks p * = 0.50 (0.39–0.61) and sub‐adults p * = 0.18 (0.10, 0.31). Estimated sex‐based differences in p o were linked to sex‐specific differences in Pr( TE ) but not in p * ; once the Pr( TE ) is accounted for, the p * between sexes was not different. These results indicate that the observed sex ratio is not a consequence of unequal detectability and sex‐specific values of Pr( TE ) are important drivers of the observed male‐dominated sex ratio. Our modeling approach reveals complex class‐specific patterns in Pr( TE ) and p * in a mark‐recapture data set, and highlights challenges for the population modeling and conservation of white sharks in central California. The model we develop here can be used to estimate rates of temporary emigration and class segregation when two detection methods are used.

Evaluating the impact and uncertainty of reservoir operation for malaria control as the climate changes in Ethiopia - Julia Reis; Teresa B. Culver; Paul J. Block; Matthew P. McCartney (Climatic Change, 2016)

Hearing thresholds of swimming Pacific bluefin tuna Thunnus orientalis - Jonathan J. Dale; Michael D. Gray; Arthur N. Popper; Peter H. Rogers; Barbara A. Block (Journal of Comparative Physiology A, 2015)

Estimating apparent survival of sub-adult and adult white sharks (Carcharodon carcharias) in central California using mark-recapture methods - Paul E. Kanive; Jay J. Rotella; Salvador J. Jorgensen; Taylor K. Chapple; Scot D. Anderson; A. Peter Klimley; Barbara A. Block (Frontiers in Marine Science, 2015)

The interplay of adult and larval time constraints shapes species differences in larval life history - Dirk J. Mikolajewski; Marjan De Block; Robby Stoks (Ecology, 2015)
In animals with a complex life cycle, larval life‐history plasticity is likely shaped by the interplay of selective factors in both larval and adult stages. A wide interspecific variation in responses to larval time constraints imposed by seasonality has been documented. Few studies have addressed differences among closely related species in the evolutionary trajectories of age and size at metamorphosis and their link with larval growth rate under time constraints. None have considered how species‐specific length of the reproductive season affects larval developmental responses to time constraints. We tested in four Coenagrion damselfly species whether species with a longer reproductive season, facing a smaller threat of missing out on reproduction, react less to larval time constraints and pre‐winter food shortage by accelerating development rate and growth rate, and therefore pay less physiological costs. All species increased development and growth rates under larval time constraints. The magnitude of this increase negatively correlated across species with the length of the reproductive season. Under larval time constraints, only the species exhibiting the longest reproductive season suffered a delayed emergence and a reduced investment in energy storage, yet also showed an increased immune function. Under a longer reproductive season, evolution may favor compensation for larval constraints after metamorphosis. Growth rate was accelerated after pre‐winter food shortage to the same extent across species; effects on age and mass at emergence also did not differ among species. Time constraints associated with the length of the reproductive season may predictably contribute to species differences in their response to time constraints imposed in the larval stage. Our study adds empirical proof that the interplay of selective factors in the larval and adult stages may determine life‐history plasticity with regard to larval time constraints.

Reconstructing transoceanic migration patterns of Pacific bluefin tuna using a chemical tracer toolbox - Daniel J. Madigan; Zofia Baumann; Aaron B. Carlisle; Danielle K. Hoen; Brian N. Popp; Heidi Dewar; Owyn E. Snodgrass; Barbara A. Block; Nicholas S. Fisher (Ecology, 2014)
Large pelagic predators play important roles in oceanic ecosystems, and may migrate vast distances to utilize resources in different marine ecoregions. Understanding movement patterns of migratory marine animals is critical for effective management, but often challenging, due to the cryptic habitat of pelagic migrators and the difficulty of assessing past movements. Chemical tracers can partially circumvent these challenges by reconstructing recent migration patterns. Pacific bluefin tuna ( Thunnus orientalis ; PBFT) inhabit the western and eastern Pacific Ocean, and are in steep decline due to overfishing. Understanding age‐specific eastward transpacific migration patterns can improve management practices, but these migratory dynamics remain largely unquantified. Here, we combine a Fukushima‐derived radiotracer ( 134 Cs) with bulk tissue and amino acid stable isotope analyses of PBFT to distinguish recent migrants from residents of the eastern Pacific Ocean. The proportion of recent migrants to residents decreased in older year classes, though the proportion of older PBFT that recently migrated across the Pacific was greater than previous estimates. This novel toolbox of biogeochemical tracers can be applied to any species that crosses the North Pacific Ocean.

Impacts of Hemlock Loss on Nitrogen Retention Vary with Soil Nitrogen Availability in the Southern Appalachian Mountains - Corinne E. Block; Jennifer D. Knoepp; Katherine J. Elliott; Jennifer M. Fraterrigo (Ecosystems, 2012)

Development of the mandibular, hyoid arch and gill arch skeleton in the Chinese barb Puntius semifasciolatus : comparisons of ossification sequences among Cypriniformes - A. J. Block; P. M. Mabee (Journal of Fish Biology, 2012)
The morphogenesis and sequence of ossification and chondrification of skeletal elements of the jaws, and hyoid arch and gill arches of Puntius semifasciolatus are described. These data provide a baseline for further studies and enable comparisons with other described cypriniforms. Some general patterns of ossification in the hyoid arch and branchial arches in cypriniforms were notable. First, the overall development is from anterior to posterior, with the exception of the fifth ceratobranchial bone, which ossifies first. Second, where ossification of iterated elements is sequential, it tends to proceed from posterior to anterior, even when more posterior chondrifications are the smallest in the series. Ossification of the ceratobranchial, epibranchial and pharyngobranchial bones tends to proceed from ventral to dorsal. The comparisons revealed small sets of skeletal elements whose ossification sequence appears to be relatively conserved across cyprinid cypriniforms. Several potentially key timing changes in the ossification sequence of the jaws, hyoid arch and gill arches were identified, such as the accelerated timing of ossification of the fifth ceratobranchial bone, which may be unique to cypriniforms.

Long-term individual identification and site fidelity of white sharks, Carcharodon carcharias, off California using dorsal fins - Scot D. Anderson; Taylor K. Chapple; Salvador J. Jorgensen; A. Peter Klimley; Barbara A. Block (Marine Biology, 2011)

Relevance of Rheological Properties of Sodium Alginate in Solution to Calcium Alginate Gel Properties - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Ira S. Buckner; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

Erratum: Rheological Evaluation of Inter-Grade and Inter-Batch Variability of Sodium Alginate - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

Rheological Evaluation of Inter-grade and Inter-batch Variability of Sodium Alginate - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2010)

Habitat and behaviour of yellowfin tuna Thunnus albacares in the Gulf of Mexico determined using pop‐up satellite archival tags - K. C. Weng; M. J. W. Stokesbury; A. M. Boustany; A. C. Seitz; S. L. H. Teo; S. K. Miller; B. A. Block (Journal of Fish Biology, 2009)
This study presents the first data on movement, habitat use and behaviour for yellowfin tuna Thunnus albacares in the Atlantic Basin. Six individuals were tracked in the Gulf of Mexico using pop‐up satellite archival tags. Records up to 80 days in length were obtained, providing information on depth and temperature preferences as well as horizontal movements. Thunnus albacares in the Gulf of Mexico showed a strong preference for the mixed layer and thermocline, consistent with findings for this species in other ocean basins. Fish showed a diel pattern in depth distribution, remaining in surface and mixed layer waters at night and diving to deeper waters during the day. The vertical extent of T. albacares habitat appeared to be temperature limited, with fish generally avoiding waters that were >6° C cooler than surface waters. The vertical and thermal habitat usage of T. albacares differs from that of bigeye Thunnus obesus and bluefin Thunnus thynnus , Thunnus orientalis and Thunnus maccoyii tunas. These results are consistent with the results of earlier studies conducted on T. albacares in other oceans.

Near real time satellite tracking of striped marlin (Kajikia audax) movements in the Pacific Ocean - John C. Holdsworth; Tim J. Sippel; Barbara A. Block (Marine Biology, 2009)

Horizontal and vertical movements of juvenile bluefin tuna ( Thunnus orientalis ) in relation to seasons and oceanographic conditions in the eastern Pacific Ocean - TAKASHI KITAGAWA; ANDRE M. BOUSTANY; CHARLES J. FARWELL; THOMAS D. WILLIAMS; MICHAEL R. CASTLETON; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Electronically tagged juvenile Pacific bluefin, Thunnus orientalis , were released off Baja California in the summer of 2002. Time‐series data were analyzed for 18 fish that provided a record of 380 ± 120 days (mean ± SD) of ambient water and peritoneal cavity temperatures at 120 s intervals. Geolocations of tagged fish were estimated based on light‐based longitude and sea surface temperature‐based latitude algorithms. The horizontal and vertical movement patterns of Pacific bluefin were examined in relation to oceanographic conditions and the occurrence of feeding events inferred from thermal fluctuations in the peritoneal cavity. In summer, fish were located primarily in the Southern California Bight and over the continental shelf of Baja California, where juvenile Pacific bluefin use the top of the water column, undertaking occasional, brief forays to depths below the thermocline. In autumn, bluefin migrated north to the waters off the Central California coast when thermal fronts form as the result of weakened equatorward wind stress. An examination of ambient and peritoneal temperatures revealed that bluefin tuna fed during this period along the frontal boundaries. In mid‐winter, the bluefin returned to the Southern California Bight possibly because of strong downwelling and depletion of prey species off the Central California waters. The elevation of the mean peritoneal cavity temperature above the mean ambient water temperature increased as ambient water temperature decreased. The ability of juvenile bluefin tuna to maintain a thermal excess of 10°C occurred at ambient temperatures of 11–14°C when the fish were off the Central California coast. This suggests that the bluefin maintain peritoneal temperature by increasing heat conservation and possibly by increasing internal heat production when in cooler waters. For all of the Pacific bluefin tuna, there was a significant correlation between their mean nighttime depth and the visible disk area of the moon.

Striped marlin ( Tetrapturus audax ) movements and habitat utilization during a summer and autumn in the Southwest Pacific Ocean - TIM J. SIPPEL; PETER S. DAVIE; JOHN C. HOLDSWORTH; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Six striped marlin ( Tetrapturus audax ) were caught on hook and line from recreational fishing boats near northern New Zealand (34°S, 174°E) and tagged and released with pop‐off satellite archival tags. For periods ranging from 22 to 60 days over the geographical range 168°E–170°W and 13–34°S, five tags collected a total of 202 days (range of 21–60 days) of data. These data permit the investigation of striped marlin geographical and vertical movements and water temperatures occupied from February to June 2003. One hundred and one days of geoposition data showed a preliminary view of their movements in and around New Zealand waters. Transmitted temperature and depth data indicated striped marlin spent 80% (±2%) of their time in the mixed layer including 72% (±2%) of their time in the top 5 m. Temperature data indicated 75% (±10%) of the striped marlin’s time was spent in water temperatures between 20.1 and 24.0°C. Tagged striped marlin moved faster during periods of directed movement away from New Zealand versus periods of passive movements when the fish were proximal to New Zealand or not moving in any specific direction. These data support some existing hypotheses about striped marlin physiological ecology and allow preliminary suggestions about how striped marlin bycatch might be reduced.

Results of satellite tagging of Atlantic bluefin tuna, Thunnus thynnus, off the coast of Ireland - Michael J. W. Stokesbury; Ronan Cosgrove; Andre Boustany; Daragh Browne; Steven L. H. Teo; Ronald K. O’Dor; Barbara A. Block (Hydrobiologia, 2007)

Annual migrations, diving behavior, and thermal biology of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre Boustany; Heidi Dewar; Michael J. W. Stokesbury; Kevin C. Weng; Shana Beemer; Andrew C. Seitz; Charles J. Farwell; Eric D. Prince; Barbara A. Block (Marine Biology, 2007)

Semiquantitative Assessment of Regional Climate Vulnerability: The North-Rhine Westphalia Study - J. p. Kropp; A. Block; F. Reusswig; K. Zickfeld; H. J. Schellnhuber (Climatic Change, 2006)

A Review of Fine Root Dynamics in Populus Plantations - R. M. A. Block; K. C. J. Van Rees; J. D. Knight (Agroforestry Systems, 2006)

Movement and environmental preferences of Greenland sharks (Somniosus microcephalus) electronically tagged in the St. Lawrence Estuary, Canada - Michael J. W. Stokesbury; Chris Harvey-Clark; Jeffrey Gallant; Barbara A. Block; Ransom A. Myers (Marine Biology, 2005)

Comparison of light- and SST-based geolocation with satellite telemetry in free-ranging albatrosses - Scott A. Shaffer; Yann Tremblay; Jill A. Awkerman; R. William Henry; Steven L. H. Teo; David J. Anderson; Donald A. Croll; Barbara A. Block; Daniel P. Costa (Marine Biology, 2005)

Characterization of Aspen ASH, Sand and Log-Yard Waste Mixtures from an Aspen-Based Oriented Strand Board Mill for Use as an Intermediate Landfill Cover - R. M. A. Block; K. C. J. van Rees (Water, Air, & Soil Pollution, 2004)

Soil arthropods as indicators of water stress in Antarctic terrestrial habitats? - Peter Convey; William Block; Helen J. Peat (Global Change Biology, 2003)
Abiotic features of Antarctic terrestrial habitats, particularly low temperatures and limited availability of liquid water, strongly influence the ecophysiology and life histories of resident biota. However, while temperature regimes of a range of land microhabitats are reasonably well characterized, much less is known of patterns of soil water stress, as current technology does not allow measurement at the required scale. An alternative approach is to use the water status of individual organisms as a proxy for habitat water status and to sample over several years from a population to identify seasonal or long‐term patterns. This broad generalization for terrestrial invertebrates was tested on arthropods in the maritime Antarctic. We present analyses of a long‐term data set of body water content generated by monthly sampling for 8–11 years of seven species of soil arthropods (four species of Acari, two Collembola and one Diptera) on maritime Antarctic Signy Island, South Orkney Islands. In all species, there was considerable within‐ and between‐sample variability. Despite this, clear seasonal patterns were present in five species, particularly the two collembolans and a prostigmatid mite. Analyses of monthly water content trends across the entire study period identified several statistically significant trends of either increase or decrease in body water content, which we interpret in the context of regional climate change. The data further support the separation of the species into two groups as follows: firstly, the soft‐bodied Collembola and Prostigmata, with limited cuticular sclerotization, which are sensitive to changes in soil moisture and are potentially rapid sensors of microhabitat water status, secondly, more heavily sclerotized forms such as Cryptostigmata (=Oribatida) and Mesostigmata mites, which are much less sensitive and responsive to short‐term fluctuations in soil water availability. The significance of these findings is discussed and it is concluded that annual cycles of water content were driven by temperature, mediated via radiation and precipitation, and constituted reliable indicators of habitat moisture regimes. However, detailed ecophysiological studies are required on particular species before such information can be used to predict over long timescales.

Effects of Fipronil and Chlorpyrifos on Endocrine-Related Endpoints in Female Grass Shrimp (Palaemonetes pugio) - D. C. Volz; E. F. Wirth; M. H. Fulton; G. I. Scott; E. Strozier; D. S. Block; J. L. Ferry; S. S. Walse; G. T. Chandler (Bulletin of Environmental Contamination and Toxicology, 2003)

Planetary habitability: is Earth commonplace in the Milky Way? - S. Franck; A. Block; W. Bloh; C. Bounama; I. Garrido; H.-J. Schellnhuber (The Science of Nature, 2001)

Depth and muscle temperature of Pacific bluefin tuna examined with acoustic and pop-up satellite archival tags - David J. Marcinek; Susanna B. Blackwell; Heidi Dewar; Ellen V. Freund; Charles Farwell; Daniel Dau; Andrew C. Seitz; Barbara A. Block (Marine Biology, 2001)

Gas and fluid venting at the Makran accretionary wedge off Pakistan - U. von Rad; U. Berner; G. Delisle; H. Doose-Rolinski; N. Fechner; P. Linke; A. Lückge; H. A. Roeser; R. Schmaljohann; M. Wiedicke; SONNE 122/130 Scientific Parties; M. Block; et al. (Geo-Marine Letters, 2000)

Factors Associated with Nosocomial Diarrhea and Clostridium difficile -Associated Disease on the Adult Wards of an Urban Tertiary Care Hospital - M. J. Schwaber; A. Simhon; C. Block; V. Roval; N. Ferderber; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Thermal tolerance and acclimation response of larvae of the sub-Antarctic beetle Hydromedion sparsutum (Coleoptera: Perimylopidae) - J. S. Bale; W. Block; M. R. Worland (Polar Biology, 2000)

Syndromes of Global Change: a qualitative modelling approach to assist global environmental management - G. Petschel-Held; A. Block; M. Cassel-Gintz; J. Kropp; M.K.B. Lüdeke; O. Moldenhauer; F. Reusswig; H.J. Schellnhuber (Environmental Modeling & Assessment, 1999)

Collembola of sub-Antarctic South Georgia - P. Convey; P. Greenslade; R. J. Arnold; W. Block (Polar Biology, 1999)

Population Responses of Peromyscus Resident in Iowa Cornfields Treated with the Organophosphorus Pesticide COUNTER® - Elizabeth K. Block; Thomas E. Lacher; Larry W. Brewer; George P. Cobb; Ronald J. Kendall (Ecotoxicology, 1999)

Spatial dynamics of two introduced species of carabid beetles on the sub-Antarctic island of South Georgia - G. J. Brandjes; W. Block; G. Ernsting (Polar Biology, 1999)

Horizontal movements and depth distribution of large adult yellowfin tuna ( Thunnus albacares ) near the Hawaiian Islands, recorded using ultrasonic telemetry: implications for the physiological ecology of pelagic fishes - R. W. Brill; B. A. Block; C. H. Boggs; K. A. Bigelow; E. V. Freund; D. J. Marcinek (Marine Biology, 1999)

Hydrology, water availability and tundra ecosystem function in a changing climate: the need for a closer integration of ideas? - I. D. Hodkinson; N. R. Webb; J. S. Bale; W. Block (Global Change Biology, 1999)
Hydrologists and ecologists studying tundra ecosystems have worked largely independently, with little cross‐fertilization between disciplines. Their disciplines are, however, inextricably linked by a need to understand the dynamics and significance of the common substance water, in its liquid, solid and gaseous state within tundra environments. The impacts of predicted long‐term changes in climate have particularly important consequences for the functioning of tundra systems and there is a pressing need to initiate studies that integrate hydrological and ecological methodologies and concepts. Our paper attempts to summarize existing information on the role of water within tundra ecosystems, to emphasize the fundamental links between the biotic and the physico/chemical environments and to suggest how a closer integration of ideas might be achieved. Given the breadth of the subject matter the paper is intended to be illustrative rather than comprehensive. The paper examines the physical impacts of water in its various states on the tundra environment, emphasizing in particular the causes of spatial variation in water availability to living organisms. The significance of water is discussed for a range of organism groups, including plants, invertebrates and microorganisms and its pivotal role in ecosystem function and disturbance stressed. The need to develop integrated hydological/ecological models for tundra systems on different spatial scales is emphasized.

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Bacterial influence on partitioning rate during the biodegradation of styrene in a biphasic aqueous-organic system - P. Osswald; P. Baveye; J. C. Block (Biodegradation, 1996)